Mary Malloy and the baby who wouldn't sleep - Daly, Niki. (New York : Artists and Writers Guild ; Racine, Wis. : Golden Books/Western Pub. Co., 1993)
The sly seductive moon makes off with a crying baby but is eventually outwitted by the clever Mr. Fez.
"First published in 1992 by Heinemann Ltd., London"--verso t.p.
Keywords: Babies -- Fiction; Moon -- Fiction